PHARMACOLOGICAL EVALUATION OF ANTIUROLITHIATIC ACTIVITY OF DOLICHOS BIFLORUS SEEDEXTRACT IN RAT’S MODEL - HAQUE, MOHIBUL; AL-SHAMI, ALI SALMAN; CHATTERJEE, SANDIPAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The main aim of the present study was to investigate the antiurolithiatic activity of Dolichos Biflorus methanolic seed extract in a rat’s model. In the phytochemical screening, it was found that Dolichos Biflorus seed extract showed the presence of tannins steroids, protein, flavonoids, terpenoids, mucilage, saponin, and carbohydrate and the absence of alkaloids fixed oil. Hence, this plant has highly diuretic activity. Methods: Model: Sodium oxalate induced urolithiasis in rats. A total of 30 rats were used for this study and the animals were divided into five groups. Each group contains six rats: Normal control group, disease control group (sodium oxalate 75 mg/kg, IP), standard group (Cystone, 750 mg/kg, PO), treatment group1 (Dolichos Biflorus 150 mg/kg, PO), treatment Group 2 (Dolichos Biflorus 300 mg/kg, PO). Urolithiasis was induced by using sodium oxalate (75 mg/kg, IP) for 28 days. Results: At the end of the experiment, all the animal blood samples were collected to check the various biochemical parameters. Animals were sacrificed by giving a high dose of pentobarbitone and kidneys were collected for antioxidant and histopathological study. From the renal function test, it was found that the drug is showing a potent effect when compared to the disease control group and standard group. Moreover, from the antioxidant and histopathology study, it was found that the drug is showing a potent effect when compared to the disease control and standard group and control group. Conclusion: After all the investigation, it was found that oral administration of Dolichos Biflorus seed extract at the low dose of 150 mg/kg and the high dose of 300 mg/kg against the sodium oxalate-induced urolithiasis and it was found that high is more effective as compared to low dose. Drug was able to suppress oxalate synthesizing enzymes and minerals. Moreover, histopathology study in the treatment group showed recovery and normal architecture of glomerulus with a tuft of capillaries surrounded by Bowman’s capsule. The most of tubules are showing normal architecture and recovery. After seeing all the results, it is confirmed that the test drug Dolichos Biflorus has potent antiurolithiatic activity. (Dolichos Biflorus short form mentioned below as DB)